TEAMWORK FOR THE SHOOTER - Scariolo, Sergio (Sport- és Egészségtudományi füzetek, 2025)
To get the benefit of a great shooter is not easy. Sometimes these players are not as creative or not great defensive play-ers. When we have a specific player, it will be demanding and challenging for the coach. Coaches have to put up good teamwork around to get the full advantage of this player, because the opponent will find a way to slow the shooter down. A team must be ready to calibrate the defensive strat-egies what the opponent will put in place to try to make the shooter less effective and react in the desired way. If the op-ponent’s defense wants to concentrate, force their energies, their strength, and their activity, to prevent him or her from taking the best shot, they will miss something on other parts of the floor or other players. That has to be recognisable and our team has to be ready for that. Therefore our shooter has to beready to become a passer in a hard stunt, a step up sit-uation or when a switching takes place. A lot of times taking the shot is not the best situation for the team but we still make opportunities for the others to play the shooter.